Offshore Currency Markets : Non-Deliverable Forwards (NDFs) in Asia - Schmittmann, Jochen M. (IMF Working Papers; Working Paper ;, 2020)
Non-deliverable forward (NDF) markets in many Asian emerging market currencies are large, rapidly growing, and often exceed onshore markets in transaction volume. NDFs tend to price significant depreciation during market stress episodes including COVID-19. Spillovers from NDFs to onshore markets are a policymaker concern. Our analysis shows that influences tend to run both ways after controlling for differences in timezones between markets. For the COVID-19 pandemic there is some evidence of NDFs leading onshore markets for a few currencies. Policy approaches to NDFs vary widely across Asia from close integration with onshore markets to severe restrictions on NDF trading.